Social and Affective Neuroscience of Everyday Human Interaction From Theory to Methodology - Boggio, Paulo Sérgio; Wingenbach, Tanja S. H.; da Silveira Coêlho, Marília Lira; Comfort, William Edgar; Murrins Marques, Lucas; Alves, Marcus Vinicius C. (Springer Nature, 2023)
This Open Access book presents the current state of the art knowledge on social and affective neuroscience based on empirical findings. This volume is divided into several sections first guiding the reader through important theoretical topics within affective neuroscience, social neuroscience and moral emotions, and clinical neuroscience. Each chapter addresses everyday social interactions and various aspects of social interactions from a different angle taking the reader on a diverse journey. The last section of the book is of methodological nature. Basic information is presented for the reader to learn about common methodologies used in neuroscience alongside advanced input to deepen the understanding and usability of these methods in social and affective neuroscience for more experienced readers.